Analisis Kalimat Teks Anekdot pada Buku Bahasa Indonesia Kelas X Kurikulum Merdeka - Laras Safitri; Winna Widyadhana; Asifah Salsadila; Mei Ismiyanti; Asep Purwo Yudi Utomo; Ramadhan Kusuma Yuda (Pusat Riset dan Inovasi Nasional, 2023)
Syntax is a branch of linguistics that studies phrases, clauses, and sentences. In this article, the focus is more on discussing the analysis of sentences in a text, in which the sentence itself is part of the syntax, namely syntactic units composed of basic constituents, usually in the form of clauses, supplemented by conjunctions when needed, and accompanied by final intonation. This article’s text is anecdotal from the Class X Indonesian Language Book of the Merdeka Curriculum. The anecdotal texts in the book are then analyzed for sentences to know whether direct or indirect sentences and sentences are standard. Analyzing a sentence certainly uses a method or method used. The method itself uses a qualitative descriptive method. The qualitative descriptive method is used to make a detailed description of a particular object which is carried out systematically, factually, and accurately. The results of this study found effective sentences, ineffective sentences, declarative sentences, interrogative sentences, and imperative sentences. Based on the results of the analysis found five anecdotal texts. This research can be used as a source of learning, for example in learning about types of sentences. In addition, it can be used to measure literacy levels. As well as b improving language competence, it can also shape students' character conceptually and in the form of humor, which has become a part of life today.